PENERAPAN MEDIA CERITA BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA SDN 01 BENGKAYANG - NainaKristina, Siprianus Jewarut (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
The media of picture stories are books that convey stories through pictures. In Grade V at SD Negeri 01 Bengkayang, there are students who are still spelling out words while reading and some who cannot yet distinguish punctuation marks in sentences. This affects the advanced reading learning in the next class. To improve students' reading skills, the researcher used learning media in the form of Picture Stories. This study aims to determine the improvement of students' reading skills using picture story media and to evaluate students' reading abilities after using the media. This research is Classroom Action Research (CAR) that uses data collection instruments in the form of teacher activity observation sheets, student activity observation sheets, reading tests, and post-tests. The results of the study showed that the application of picture story media can improve students' reading skills and their enthusiasm in the learning process. Moreover, students' reading abilities also significantly improved, as evidenced by achieving scores above the Minimum Competency Criteria (KKM). This study concludes that picture story media is effective in improving the reading skills of Grade V students at SD Negeri 01 Bengkayang. Therefore, it is suggested that teachers implement picture story media in Indonesian language lessons during the learning process to achieve better results.